Infant quantitative risk for autism spectrum disorder predicts executive function in early childhood. Issue 11 (21st October 2018) - Stephens, Rebecca L.; Watson, Linda R.; Crais, Elizabeth R.; Reznick, J. Steven
Abstract : Much of the current research concerning autism spectrum disorder (ASD) focuses on early identification of behaviors that may indicate future deficits or higher risk for a later diagnosis. Additionally, there exists a strong claim regarding the dimensional nature of ASD, such that even among non‐diagnosed individuals, a continuous distribution of symptom severity can be observed. Executive function (EF) has been widely studied in children, adolescents, and adults with ASD, with a robust body of research supporting widespread EF deficits in diagnosed individuals. However, it remains unclear how the degree of ASD symptomatology, outside of the presence of a diagnosis, affects EF abilities in a community sample. The First Year Inventory 2.0 (FYI 2.0), a parent‐report measure, was designed to identify infants at 12 months who are at risk for an eventual ASD diagnosis. In the current study, a continuous scoring scale was used to examine risk (overall, Social‐Communication, and Sensory‐Regulatory) from a dimensional perspective. Parents also completed the Behavior Rating Inventory of Executive Function‐Preschool Version and the Social Responsiveness Scale‐2nd edition when their children were 42 months (3.5 years) old. Each FYI 2.0 risk variable significantly predicted scores on an overall EF composite and specific EF subscales. When controlling for general ASD symptomatology, Sensory‐Regulatory risk still significantly predicted EF deficits. This research provides additional support for a quantitative consideration of risk for ASD and presents novel findings regarding the relation between infant behaviors indicative of ASD risk and EF in early childhood. Autism Research 2018, 11: 1532–1541 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Children with autism spectrum disorder (ASD) often have difficulty with executive function (EF) tasks that require a set of mental processes involved in goal‐directed behaviors. Studying children without ASD who may have symptoms affecting EF is also important. This study demonstrates that certain infant behaviors related to ASD are linked to early childhood EF difficulties. These results support looking at a range of ASD symptoms to better understand children who struggle with EF and potentially design tools to help them.